Penerapan Manajemen Strategi Pada UMKM Samosa Mubels Di Meulaboh - Tia Yumaida (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in the regional economy, yet they still face various challenges such as limited resources, increasing competition, and the need to adapt to technological developments. One way MSMEs can survive and thrive is through the implementation of appropriate strategic management. This study aims to analyze the implementation of strategic management at the Samosa Mubels MSME in Meulaboh to increase competitiveness and business sustainability. The research method used was a qualitative descriptive approach, with data collection through in-depth interviews with business owners. The results indicate that the Samosa Mubels MSME has implemented strategic management in stages, taking into account both internal and external business conditions. The strategies implemented include emphasizing product quality, raw material consistency, utilizing social media as a marketing tool, and product differentiation through unique flavors. Despite facing challenges such as business competition and limited capital, the implementation of strategic management has helped the Samosa Mubels MSME increase product visibility and build relationships with customers. The implementation of sustainable strategic management is expected to increase the competitiveness of MSMEs and support local economic growth.